Feasibility, long‐term safety, and immune monitoring of regulatory T cell therapy in living donor kidney transplant recipients. Issue 4 (2nd February 2021) - Harden, Paul N.; Game, David S.; Sawitzki, Birgit; Van der Net, Jeroen B.; Hester, Joanna; Bushell, Andrew; Issa, Fadi; Brook, Matthew O.; Alzhrani, Alaa; Schlickeiser, Stephan; Scotta, Cristiano; Petchey, William; et al.
Abstract: Short‐term outcomes in kidney transplantation are marred by progressive transplant failure and mortality secondary to immunosuppression toxicity. Immune modulation with autologous polyclonal regulatory T cell (Treg) therapy may facilitate immunosuppression reduction promoting better long‐term clinical outcomes. In a Phase I clinical trial, 12 kidney transplant recipients received 1–10 × 10 6 Treg per kg at Day +5 posttransplantation in lieu of induction immunosuppression (Treg Therapy cohort). Nineteen patients received standard immunosuppression (Reference cohort). Primary outcomes were rejection‐free and patient survival. Patient and transplant survival was 100%; acute rejection‐free survival was 100% in the Treg Therapy versus 78.9% in the reference cohort at 48 months posttransplant. Treg therapy revealed no excess safety concerns. Four patients in the Treg Therapy cohort had mycophenolate mofetil withdrawn successfully and remain on tacrolimus monotherapy. Treg infusion resulted in a long‐lasting dose‐dependent increase in peripheral blood Tregs together with an increase in marginal zone B cell numbers. We identified a pretransplantation immune phenotype suggesting a high risk of unsuccessful ex‐vivo Treg expansion. Autologous Treg therapy is feasible, safe, and is potentially associated with a lower rejection rate than standard immunosuppression. Treg therapy may provide an exciting opportunity to minimize immunosuppression therapy and improve long‐term outcomes. Abstract : Immune modulation with autologous polyclonal regulatory T cells is feasible, safe, and allows successful living donor kidney transplantation with reduced immunosuppression.